Facilitating Cross-Border Family Life - Towards a Common European Understanding EUFams II and Beyond - Pfeiffer, Thomas; Lobach, Quincy C.; Rapp, Tobias (Heidelberg University Publishing (heiUP), 2021)
This volume constitutes the final study of EUFams II, a research project on European family and succession law funded by the European Commission. Its contributors present historical developments, discuss the status quo, and draw the lines along which European family and succession law may develop in the near future. The volume endeavors to inspire its readership and the scientific community at large to engage in further research along and across these lines.